Management Decision Making Under Uncertainty: An Introduction to Probability and Statistical Decision Theory (Book). - Sterling, Robert R.; Ball, Ray (The Accounting Review, 1970)
Reviews the book "Management Decision Making Under Uncertainty: An Introduction to Probability and Statistical Decision," by T.R. Dyckman, S. Smidt and A.K. McAdams.